The Fear‐avoidance Components Scale (FACS): Development and Psychometric Evaluation of a New Measure of Pain‐related Fear Avoidance. Issue 4 (31st July 2015) - Neblett, Randy; Mayer, Tom G.; Hartzell, Meredith M.; Williams, Mark J.; Gatchel, Robert J.
Abstract: Pain‐related fear avoidance (FA), a common problem for patients with painful medical conditions, involves pain‐related catastrophizing cognitions, hypervigilance, and avoidance behaviors, which can ultimately lead to decreased functioning, depression, and disability. Several patient‐reported instruments have been developed to measure FA, but they have been criticized for limited construct validity, inadequate item specificity, lack of cutoff scores, and missing important FA components. The Fear‐Avoidance Components Scale (FACS) is a new patient‐reported measure designed to comprehensively evaluate FA in patients with painful medical conditions. It combines important components of FA found in prior FA scales, while trying to correct some of their deficiencies, within a framework of the most current FA model. Psychometric evaluation of the FACS found high internal consistency (α = 0.92) and high test/retest reliability ( r  =   0.90–0.94, P  < 0.01). FACS scores differentiated between 2 separate chronic pain patient samples and a nonpatient comparison group. When clinically relevant severity levels were created, FACS severity scores were highly associated with FA‐related patient‐reported psychosocial and objective lifting performance variables. These results suggest that the FACS is a psychometrically strong and reliable measure that can help healthcare providers assess FA‐related barriers to function and recovery.